Parallel two-Point Explicit Block method for solving high-order Ordinary Differential Equations. (6th March 2007) - Omar, Zurni; Suleiman, Mohamed B.
The derivation of a new parallel two-Point Explicit Block (2PEB) method for solving dth-order Ordinary Differential Equations (ODEs) directly is presented. The computational advantages of using this technique over the conventional one-point method are discussed. Numerical results suggest that the parallel 2PEB method is superior when used for solving second-order ODEs directly with small step size.